Distributed video coding of secure compressed sensing. Issue 14 (23rd August 2013) - Zhang, Baoju; Lei, Qing; Wang, Wei; Mu, Jiasong; Liang, Qilian; Ren, Jian; Liang, Jing; Zhang, Baoju; Pi, Yiming; Zhao, Chenglin
Abstract In this paper, we use the distributed compressed sensing to deal with video coding. To reduce the orthogonal matching pursuit algorithm computational complexity, we use the quantum‐behaved particle swarm optimization algorithm to reconstruct video signal. In this paper, we analyze the computational complexity of two algorithms, simulation results demonstrate that quantum‐behaved particle swarm optimization algorithm greatly reduce the amount of computation. And it has better stability and faster convergence to deal with original video signal. Simulation results demonstrate that we can obtain the better reconstructed video with low sample value, and it can guarantee safety performance. Copyright © 2013 John Wiley & Sons, Ltd.